2008
DOI: 10.1007/s10811-008-9374-9
|View full text |Cite
|
Sign up to set email alerts
|

Antifoulant diterpenes produced by the brown seaweed Canistrocarpus cervicornis

Abstract: This paper reports the antifouling properties of the dichloromethane crude extract (DC) and 3 pure compounds isolated from the Brazilian brown seaweed Canistrocarpus cervicornis against establishment of the mussel Perna perna. DC extract showed a strong inhibition activity against byssal threads. Two natural dolastanes and one seco-dolastane diterpene, namely (4R, 9S, 14S)-4α-acetoxy-9β,14α-dihydroxydolast-1(15),7-diene (1), (4R,7R,14S)-4α,7α-diacetoxy-14-hydroxydolast-1(15),8-diene (2) and isolinearol (3), we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 33 publications
0
25
0
1
Order By: Relevance
“…These molecules are the products of secondary metabolism and display pharmacological properties (Mayer et al, 2007;Cirne-Santos et al, 2008;Abrantes et al, 2010) as well as ecological functions (Bianco et al, 2009). A previous study demonstrated that L. muta venom displayed phospholipase A 2 (indirect hemolytic activity), hemorrhagic, clotting and proteolytic activities (Fuly et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These molecules are the products of secondary metabolism and display pharmacological properties (Mayer et al, 2007;Cirne-Santos et al, 2008;Abrantes et al, 2010) as well as ecological functions (Bianco et al, 2009). A previous study demonstrated that L. muta venom displayed phospholipase A 2 (indirect hemolytic activity), hemorrhagic, clotting and proteolytic activities (Fuly et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…The brown seaweed Canistrocarpus cervicornis (Kützing) De Paula & De Clerck (formely Dictyota cervicornis Kützing) possesses a biosynthetic pathway that produces dolastane and seco-dolastane diterpenes, encompassing a total of more than 25 compounds (Teixeira et al, 1986;de Oliveira et al, 2008). Not surprisingly, some of these diterpenes are biologicallyactive molecules (Bianco et al, 2009;Moura et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that this alga produces mainly dolastane and secodolastane diterpenes, which exhibit antiviral (Vallim et al 2010), antiophidian (Santos et al 2011), and antileishmanial (Moura et al 2011) activities. Furthermore, C. cervicornis produces diterpenes capable of inhibiting mussel byssal formation (Bianco et al 2009). In our study, Padina sp.…”
Section: Discussionmentioning
confidence: 99%
“…Dolabelane, isolated from the Brazilian brown alga Canistrocarpus cervicornis, inhibits mussel byssus formation, whereas pachydictiane, from the brown alga Dictyota sp., inhibits the growth of biofilm-forming bacteria. 22,23) Briarane diterpenes discovered in the South China Sea gorgonian Junceella juncea have antifouling activity against barnacle cyprids. 24,25) The literature indicates that diterpenes have promising antifouling activity.…”
Section: Discussionmentioning
confidence: 99%